Pengaruh Edukasi Media Power Point dan Lagu Terhadap Pengetahuan Serta Sikap Konsumsi Sayur dan Buah Siswa - Rosmita Sari; Debby Endayani Safitri; Yuli Dwi Setyowati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The prevalence of vegetable and fruit eating habits <5 servings a day in children aged ? 5 years in Banten Province is 97%. This figure is greater than the national figure of 95.5% (Riskesdas, 2018). Lack of access to information in children can result in children's knowledge and attitudes are also not good towards vegetable and fruit consumption. This study aims to improve the knowledge and attitudes of students of SDN Cireundeu 01 about vegetable and fruit consumption using power point media and songs. This education is given to students aged 11-12 years, because at that age children are considered to be able to think abstractly according to Jean Piaget's Theory. Experimental research with sampling technique, namely Pusposive Sampling. The study used data analysis with the Paired T-test and Wilcoxon Test to determine the average difference in pre-test and post-test values. In the power point group, the knowledge level of p value 0.150 means that there is no significant difference, while the attitude of p value 0.538 means that there is no significant difference. In the song group, the knowledge level of p value 0.005 means that there is a significant difference, while the attitude of p value 0 means that there is a significant difference. Education with songs has a higher mean difference than education with a power point at the student's knowledge level of 7.38. In addition, education with songs also has a higher mean difference than education with a power point on the change in student attitudes by 0.295.